1998
DOI: 10.1063/1.122797
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoresistance near the magnetostructural transition in Gd5(Si1.8Ge2.2)

Abstract: Zero-field electrical resistivity over the temperature range of 4–300 K and magnetoresistance in magnetic fields of up to 12 T have been measured in Gd5(Si1.8Ge2.2). This system undergoes a first-order magnetostructural transition at TC≅240 K, from a high-temperature paramagnetic to a low-temperature ferromagnetic phase, accompanied by a large drop in the resistivity. The application of an external magnetic field above TC can induce this transition, and a giant negative magnetoresistance effect (Δρ/ρ≅−20%) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(147 citation statements)
references
References 23 publications
5
142
0
Order By: Relevance
“…The variation of magnetization with temperature has shown that in this alloy the Curie point occurs at 110 K compared with 268 K in Gd 5 Si 2 Ge 2 . 10 The variation of magnetization as a function of magnetic field shows that the a axis is the magnetic easy axis, with a magnetocrystalline anisotropy of approximately 8.8ϫ 10 7 J/m 3 and a saturation magnetization of M s = 200 emu/ g ͑which with a density of 7.6 gm/ cm 3 gives M s = 1520 emu/ cm 3 , or 1.52ϫ 10 6 A/m͒. This compares with Gd 5 Si 2 Ge 2 which has the b axis as the easy axis with a lower anisotropy of 4.1ϫ 10 4 J/m 3 and a saturation magnetization of M s = 0.6ϫ 10 6 A/m ͑600 emu/ cm 3 ͒.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation of magnetization with temperature has shown that in this alloy the Curie point occurs at 110 K compared with 268 K in Gd 5 Si 2 Ge 2 . 10 The variation of magnetization as a function of magnetic field shows that the a axis is the magnetic easy axis, with a magnetocrystalline anisotropy of approximately 8.8ϫ 10 7 J/m 3 and a saturation magnetization of M s = 200 emu/ g ͑which with a density of 7.6 gm/ cm 3 gives M s = 1520 emu/ cm 3 , or 1.52ϫ 10 6 A/m͒. This compares with Gd 5 Si 2 Ge 2 which has the b axis as the easy axis with a lower anisotropy of 4.1ϫ 10 4 J/m 3 and a saturation magnetization of M s = 0.6ϫ 10 6 A/m ͑600 emu/ cm 3 ͒.…”
Section: Discussionmentioning
confidence: 99%
“…A number of pseudobinary compounds R 5 ͑Si x Ge 4−x ͒, where R is La, Lu, Gd, Nd, or Dy, have been investigated by Gschneidner et al 1 The alloy Gd 5 ͑Si x Ge 1−x ͒ 4 which has received much attention recently has several unique properties including a giant magnetocaloric effect, 2 giant magnetoresistance, 3 and giant magnetostriction. 4 Morellon et al 5,6 have investigated phase transitions and the magnetocaloric effect in the alloys with R = Tb and Thuy et al 7 have studied both magnetic properties and magnetocaloric effect in polycrystalline samples with specific compositions Tb 5 ͑Si 2 Ge 2 ͒ and Tb 5 ͑Si 3 Ge 1 ͒.…”
Section: Introductionmentioning
confidence: 99%
“…The field-induced, reversible nature of the magnetostructural transition then results in strong magnetostriction 14 and giant ͑negative͒ magnetoresistance. 16 For xр0.2, a second-order PM-toantiferromagnetic ͑AFM͒ transition occurs at T N ͑from ϳ125 K for xϭ0 to ϳ135 K for xϭ0.2). 6 Upon further cooling, a first-order AFM-FM transition takes place, whose temperature ranges linearly from about 20 K (xϭ0) to 120 K (xϭ0.2).…”
mentioning
confidence: 99%
“…This is because of their interesting physical properties, such as the giant magnetocaloric effect, 1-4 colossal magnetostriction, [5][6][7][8] giant magnetoresistance, [9][10][11][12][13][14][15][16] and spontaneous generation of voltage ͑SGV͒, 17 that have been observed during the firstorder magnetostructural, ferromagnetic-orthorhombic to paramagnetic-monoclinic ͑on heating͒, phase transformation ͑see Refs. 5,18͒.…”
mentioning
confidence: 99%